Strategi Penanganan Kasus Pelecehan pada Dinas Pemberdayaan Perempuan dan Perlindungan Anak (DP3A) di Kota Pekanbaru - Ridho Mahesa; Vesti Septiani; Elly Nielwaty (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2025)
This research aims to analyze and explain how the strategy in handling cases of harassment carried out by DP3A and explain what are the obstacles in overcoming this case at DP3A in Pekanbaru. Harassment cases are serious problems that require special attention in Pekanbaru City. The problem in this case is the high rate of violence against women and children that occurs, requiring the government to respond by providing protection to women and children as victims of violence. Through a Descriptive approach and literature study, this research analyzes in depth the strategy of handling sexual harassment cases implemented by DP3A. By referring to the strategy stage model according to Andrew (2011), this study identifies the obstacles faced at each stage, from formulation to assessment. The results show that although significant efforts have been made, there are still several aspects that need to be improved, such as community service, case management, as well as handling social stigma and limited resources. These findings are expected to be valuable input for DP3A in developing more effective strategies in protecting victims of sexual harassment. Analysis of the case management indicators shows that although there are some good practices, there are still gaps in terms of community education.